Photoactivatable plant hormone-based chemical inducers of proximity for in vivo applications - Pöschko, Philipp; Berrou, Caroline M.; Pakari, Kaisa; Ziegler, Michael J.; Kern, Christoph; Koch, Birgit; Wittbrodt, Joachim; Wombacher, Richard (ACS chemical biology, 2025)
Protein interactions play a crucial role in regulating cellular mechanisms, highlighting the need for effective methods to control these processes. In this regard, chemical inducers of proximity (CIPs) offer a promising approach to precisely manipulate protein-protein interactions in live cells and in vivo. In this study, we introduce pMandi, a photocaged version of the plant hormone-based CIP mandipropamid (Mandi), which allows the use of light as an external trigger to induce protein proximity in live mammalian cells. Furthermore, we present opabactin (OP) as a new plant hormone-based CIP that is effective in live mammalian cells at low nanomolar concentration and in live medaka embryos at submicromolar concentration. Its photocaged derivative, pOP, enables the induction of protein proximity upon light exposure in individual cells, enhancing spatiotemporal control to the level of single-cell resolution. Additionally, we explored the use of both photocaged CIPs to promote protein proximity in live medaka embryos.
Gesehen am 25.08.2025